PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PT TENO SUKSES ABADI DI KOTA BATAM - Nanda, Marini Tree; Wangdra, Yvonne (SCIENTIA JOURNAL, 2021)
Customer is the important things that must be considered for a company. The purpose of this study was to determine the effect of facilities and service quality on customer satisfaction at PT Teno Sukses Abadi. The number of samples used in this study were 124 people and the respondents were customers of PT Teno Sukses Abadi by using a purposive sampling technique. The method used in this research is quantitative and multiple linear regression analysis. The results showed that facilities and service quality had effect of 86,4% toward customer satisfaction. Facilities had a positive effect toward customer satisfaction with score 22,449 > t tabel 1,980 and significant with a sig t-score 0,000 < 0,050. While the service quality has a positive effect toward customer satisfaction with score 14,427 > t tabel 1,980 and significant with a sig t-score 0,000 < 0,050. Then simultaneously facilities and service quality have a significant effect with score 0,000 F-table 3,070 toward customer satisfaction. Conclusion, Partially facilities and service quality has a positive and significant effect toward customer satisfaction and simultaneously facilities and service quality have a significant effect toward the customer satisfaction at PT Teno Sukses Abadi.